Arqueología de cazadores recolectores del sector centro-oriental de la región pampeana - Loponte, Daniel (2003)
The wetland located in the Central-East of the Pampean region, associated with the Parana and Rio de la Plata rivers, shows a complex archaeological record, dated between 1640 and 680 YBP, suggesting an important concentration of hunter-gatherers population. The production of non transportable equipment like pottery, the use of bipolar reduction and selectivity of preys belonging to the wetland, suggest a low mobility and small home ranges. Fishes are the main prey in all the sites placed in the wetland. The arrival of Amazonian horticulture groups, probably increased significantly the social complexity of the area.